Respuesta :
Answer:
x^2 - 6x + __9__ = -13 + __9___
Step-by-step explanation:
x^2 - 6x + ____ = -13 + _____
To complete the square
we take the coefficient of the x term, divide by 2 and square it
-6 /2 = -3
Then square it
(-3)^2=9
What we add to one side, we add to the other
x^2 - 6x + __9__ = -13 + __9___
Answer:
x^2 - 6x + 9 = -13 + 9
Step-by-step explanation:
x^2 - 6 + ____ = -13 + _____
I assume that the second term is -6x, not just -6.
x^2 - 6x + ____ = -13 + _____
To complete the square, take the x-term coefficient, -6, halve it, -3, and then square it, (-3)^2 = 9. Now add 9 to both sides.
x^2 - 6x + 9 = -13 + 9